Association of the characteristics of pregnant women and their decision to enroll in a hospital-based umbilical cord stem cell program - Carino-Paredes, Jessa-Mae
Stem cells are cells that are czpable of renewing themselves and they can be engineered to become organ specific cells which can be used for treatment of certain conditions. There are different sources of stem cells and in the Philippines, bone marrow, umbilical cord and peripheral blood stem cells are the only ones that are permitted to be used by the Department of Health. This study aims to (1) Determine the socio-demographic characteristics of women in the sample population, including who joined / did not join the UCSCP; (2) Determine the binary relationship of the decision to enroll under the UCSCP and specific maternal characteristics included in the study and (3) Determine the maternal characteristics that are significantly associated to maternal decision to enroll under the UCSCP. A structured questionnaire was used to allow collection of specific information about patients who delivered (Normal / Caesarian) in the hospital for months November, 2016 to February, 2017). Considering all maternal characteristics, the result yielded significant P-values for Employment status and room type ? both of which can be associated with the individuals? economic status. Other weakly associated variables are age (younger) and information given by a nurse. The result may have management implications especially in terms of revisiting the vision of the UCSCP program. Package payment design, and protocols on how patients are informed about the UCSCP.